Taâ€™thÄ«r IstikhdÄm WasÄ«lah Scrabble fÄ« Tarqiyyati ItqÄni Al- MufradÄt LadÃ¡ Al-á¹¬ullÄb bi Al-Madrasah Al-MutawassiÅ£ah Al-IslÄmiyyah Al-á¸¤ukuÌ„miyyah 6 Agam - Hariati, Riti; Yusra, Oktarina (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Researchers found several problems in the process of learning vocabulary for 7th grade students at MTSN 6 Agam. Most students found it difficult to memorize the vocabulary and to master it. There are interesting learning media that can be taught during students learning vocabulary. In this study, the researchers used experimental quantitative research with a true experimental design using pretest-posttest control group design. The total populations were 155 students and the samples were 63 students using a random sampling technique. The data analysis technique used statistical analysis using spss20. The results of the study showed that there was the effect of using scrabble media on increasing students' vocabulary mastery. The average post-test score for the experimental class was 67.5 and the average for the pretest for the control class was 60.48. And the researcher found 2 tailed sig values 0.44 and 0.46, and both values were smaller than 0.05. So it can be concluded that there were differences between the two classes.ÙˆØ¬Ø¯Øª Ø§Ù„Ø¨Ø§ØØ«Ø© Ø§Ù„Ù…Ø´ÙƒÙ„Ø§Øª ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª Ù„Ø¯Ù‰ Ø·Ù„Ù‘Ø§Ø¨ Ø§Ù„ÙØµÙ„ Ø§Ù„Ø³Ù‘Ø§Ø¨Ø¹ Ø¨Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ù…ØªÙˆØ³Ù‘Ø·Ø© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠÙ‘Ø© Ø§Ù„ØÙƒÙˆÙ…ÙŠÙ‘Ø© 6 Ø¢ØºØ§Ù…. ÙƒØ«ÙŠØ± Ù…Ù† Ø§Ù„Ø·Ù‘Ù„Ù‘Ø§Ø¨ ÙŠØ´Ø¹Ø±ÙˆÙ† Ø¨ØµØ¹ÙˆØ¨Ø© ÙÙŠ ØÙØ¸ Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª ÙˆÙÙŠ ØªØ±Ù‚ÙŠÙ‘Ø© Ø¥ØªÙ‚Ø§Ù†Ù‡Ø§. ÙˆÙ„Ù… ØªÙˆØ¬Ø¯ Ø§Ù„ÙˆØ³Ø§Ø¦Ù„ Ø§Ù„ØªÙ‘Ø¹Ù„ÙŠÙ…ÙŠÙ‘Ø© Ø§Ù„Ø¬Ø°Ø§Ø¨Ø© ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª. Ø§Ù„Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„Ù…Ø³ØªØ®Ø¯Ù…Ø© ÙÙŠ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡ÙŠ Ø·Ø±ÙŠÙ‚Ø© ÙƒÙ…ÙŠØ© Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… Ù…Ø¯Ø®Ù„Â Ø´Ø¨Ù‡ ØªØ¬Ø±Ø¨Ø© Ø¨Ù†ÙˆØ¹ Ù…Ù‚Ø§Ø±Ù†Ø© Ø§Ù„Ø¨ØØ« Ø¨ÙŠÙ† Ø§Ù„ÙØµÙ„ Ø§Ù„ØªØ¬Ø±ÙŠØ¨ÙŠ ÙˆØ§Ù„ÙØµÙ„ Ø§Ù„Ø¶Ø§Ø¨Ø· Â Â True Eksperimental DesignØ¨Ø§Ù„Ù†Ù‘ÙˆØ¹ Pretest-Posttest Control Group Design. Ù†ØªØ§Ø¦Ø¬ Ø§Ù„Ø¨ØØ« Ù‡ÙŠ Ù‡Ù†Ø§Ùƒ ØªØ£Ø«ÙŠØ± Ø§Ø³ØªØ®Ø¯Ø§Ù… ÙˆØ³ÙŠÙ„Ø© Ø³ÙƒØ±Ø§Ø¨Ù„ Ø¹Ù„Ù‰ ØªØ±Ù‚ÙŠÙ‘Ø© Ø¥ØªÙ‚Ø§Ù† Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª. ÙƒØ§Ù†Øª Ù†ØªÙŠØ¬Ø© ØØ³Ø§Ø¨ Ù…ØªÙˆØ³Ù‘Ø· Ø§Ù„Ø§Ø®ØªØ¨Ø§Ø± Ø§Ù„Ø¨Ø¹Ø¯ÙŠ ÙÙŠ Ø§Ù„ÙØµÙ„ Ø§Ù„ØªÙ‘Ø¬Ø±ÙŠØ¨ÙŠ 67ØŒ5 ÙˆØ£Ù…Ù‘Ø§ Ù†ØªÙŠØ¬Ø© ØØ³Ø§Ø¨ Ù…ØªÙˆØ³Ù‘Ø· Ø§Ù„Ø§Ø®ØªØ¨Ø§Ø± Ø§Ù„Ù‚Ø¨Ù„ÙŠ ÙÙŠ Ø§Ù„ÙØµÙ„ Ø§Ù„Ø¶Ù‘Ø§Ø¨Ø· 60ØŒ48. ÙˆØªÙˆØ¬Ø¯ Ù‚ÙŠÙ…Ø© Ø§Ù„Ø£Ù‡Ù…ÙŠÙ‘Ø© (Sig 2-Tailed)0ØŒ44 Ùˆ0ØŒ46 Ø£ØµØºØ± Ù…Ù† 0ØŒ05. Ùˆ ØªØ®Ù„Øµ Â Ø£Ù†Ù‘ Ù‡Ù†Ø§Ùƒ ÙØ±Ù‚Ø§ Ø¨ÙŠÙ† Ø§Ù„ÙØµÙ„ÙŠÙ†.Â